KANDUNGAN NITRAT DAN POSPAT SEBAGAI FAKTOR TINGKAT KESUBURAN PERAIRAN PANTAI - Arif Mustofa (Universitas Islam Nahdlatul Ulama Jepara, 2015)
ABSTRACT Phytoplankton is a biological indicator to evaluate the water quality. Phytoplankton productivity is depended on inorganic nitrogen as nitrate (NO3) and phosphorus as phosphate (PO4). The purpose of observation on nitrate and phosphate content as a factor in fertility rates coastal waters. The benefits of this observation is to provide information to support the coastal cultivation. Sampling was conducted on August 13, 2014 at 10:00 am in the coastal waters of Tanggultlare Kedung Jepara, consists of three stations, namely the waters near mangrove vegetation, muddy beach and near the mouth of the river. Sample analysis conducted at the BBPBAP Jepara Laboratory. The analysis data shows that the location is the waters near mangrove containing NO3 1.392 mg/ltr, muddy beach 0.975 mg/ltr and at the mouth of the river 0.904 mg/ltr with an average of 1,090 mg/ltr. While the value of PO4 location the waters near mangrove containing 0.095 mg/ltr, muddy beach 0.089 mg/ltr and at the mouth of the river 0,087 mg/ltr with an average of 0.090 mg/ltr. The average of nitrate 1.090 mg/ltr indicates that the level of fertility waters are mesotrofik and phosphate (PO4) of 0.090 mg/ltr is eutrophic. Keywords: nitrate, phosphate, fertility, phytoplankton, Tanggultlare ABSTRAK Phytoplankton merupakan indikator biologis untuk mengevaluasi kualitas air. Produktivitas phytoplankton tergantung dari nitrogen inorganik seperti nitrat NO3) and phosphorus sebagai fosfat (PO4). Tujuan obsevasi pada isi nitrat dan fosfat sebagai faktor tingkat kesuburan perairan pantai. Keuntungan dari observasi ini untuk memberikan informasi mendukung penanaman area pantai. Pengambilan sampel dilakukan pada tanggal 13 Agustus 2014 jam 10:00 a.m di perairan pantai Tanggultlare Ked ung Jepara di tiga tempat yaitu perairan dekat vegetasi mangrove, tanah berlumpur, dan dekat mulut sungai. Analisa sampel dilakukan di laboratorium BBPAP Jepara. Data analisis menunjukkan bahwa di lokasi perairan sekitar mangrove mengandung NO3 1.392 mg/ltr, tanah lumpur 0.975 mg/ltr dan di mulut sungai 0.904 mg/ltr dengan rata-rata 1,090 mg/ltr. Rata-rata nitrat 1.090 mg/ltr mengindikasikan bahwa tingkat kesuburan di area peairan merupakan are mesotrofik and mengandung eutrofik fosfat (PO4) of 0.090 mg/ltr. Kata Kunci: nitrate, phosphate, fertility, phytoplankton, Tanggultlare